Isolation, purification, and characterization of xylanase produced by aspergillus niger in solid state fermentation - SHABEENA ANJUM K S,; RAVI M,; Y M JAYARAJ, (International Journal of Pharma and Bio Sciences, 2017)
Globally xylanase which aids in the hydrolysis of xylan, the major hemicelluloses of plant cell wall, is extensively used in in the environmental friendly technologies. In comparison to bacteria and yeasts, fungi are usually considered as more potent producers of xylanases and hence, they are extensively used as xylanase producers. Considering the industrial significance of xylanases, a significant number of studies are reported on cloning and expression of the enzymes during the last few years. With its wide application in the economy, the objective of the present study was to isolate and characterize xylanase produced by Aspergillus niger when grown in solid state fermentation. The crude extract of xylanase produced by Aspergillus niger was 44.85 IU, while the ammonium sulphate precipitated and dialysis extract of xylanase were 33.63 IU and 19.78 IU respectively. This implies that the protein content was found to be higher in crude extract followed by to Ammonium sulphate precipitated and dialysis. The molecular weight of xylanase was found to be 31,000 ± 2000 as determined by using Sephadex G-200 gel filtration chromatography according to the procedure of Whitaker. On sodium dodecyl sulfate poly acrylamide gel electrophoresis, the subunit molecular weight of xylanase in single band obtained was ~31,000 and this indicated the monomeric nature of the enzyme. Using 18s rRNA gene primers, ~1.1Kb gene was amplified from the isolated genomic DNA. PCR product obtained was gel purified and quantitated and also sequenced. The sequence data obtained was analyzed and consensus sequence generated from forward and reverse sequences using aligner software was subjected to BLAST with NCBI genbank database. Based on maximum identity score, first five identities were considered and the culture was identified. Phylogenic tree was also constructed for these sequences.